(untitled) (Okhaldhunga Journal, 2025)
Welcome to the second volume of Okhaldhunga Journal, published by Okhaldhunga Campus. As we present this latest edition, we are filled with pride and excitement about the growing academic discourse within our institution and beyond. This second publication marks a significant milestone in our campus’s progress towards fostering a vibrant research community. It reflects the ongoing commitment of our faculty, students, and collaborators to contribute valuable scholarship across diverse fields. In this volume, readers will discover a rich array of articles that demonstrate the depth and breadth of our research. Each article has been carefully selected for its scholarly merit and relevance, ensuring this volume is both informative and stimulating. We extend our sincere gratitude to all authors who have generously shared their research for this volume. Their hard work and insights are the cornerstone of this publication. We also thank our peer reviewers for their rigorous evaluation, which has upheld the quality and integrity of the articles presented here. As we build upon the foundation laid by our inaugural issue, we encourage readers to critically engage with the ideas presented within these pages. We aspire for this journal to ignite discussions, inspire further research, and contribute meaningfully to the broader academic conversation. Looking ahead, we are committed to expanding the scope and impact of Okhaldhunga Journal. We invite submissions for upcoming volumes and encourage readers to share their feedback to help us improve and grow. Please visit the submission guidelines. Thank you for your support of Okhaldhunga Journal. We hope you find this volume enlightening and thought-provoking.